O PODER DA LIBERDADE: EM BUSCA DE ESTRATÉGIAS DEMOCRÁTICAS DE PUBLICAÇÃO ACADÊMICA. - Blommaert, Jan (Trabalhos em Lingüística Aplicada)
In this essay, Jan Blommaert discusses fundamental issues on the economic dimension of academic publishing, the reasons and the intentions for publishing as an academic, and the available alternatives. The author presents the conditions of the productive cycle of academic journal publishers and argues that the business model is based on the threefold exploitation of academics' work, as authors, reviewers, and readers of the articles, and of the institutions and governments who fund the published research. The author criticizes the false solution of "gold" and "green" access and expose the impact of new modes of circulation on the cheapening and high reaches of academic communication. He defends democratic strategies of academic publishing led by the people who do research and argues for our autonomy to promote the primary function of academic publishing: the debate of ideas with the largest possible number of experts in the field.